Analysis of expression profiles of genes involved in F(o)F(1)-ATP synthase biogenesis during perinatal development in rat liver and skeletal muscle - Spáčilová, Jana; Hůlková, Martina; Hruštincová, Andrea; Čapek, Václav; Tesařová, Markéta; Hansíková, Hana; Zeman, Jiří (Physiological research, 2016)
During the process of intra-uterine mammalian fetal development, the oxygen supply in growing fetus is low. A rapid switch from glycolysis-based metabolism to oxidative phosphorylation (OXPHOS) must proceed during early postnatal adaptation to extra-uterine conditions. Mitochondrial biogenesis and mammalian mitochondrial F(o)F(1)-ATP synthase assembly (complex V, EC 3.6.3.14, ATPase) are complex processes regulated by multiple transcription regulators and assembly factors. Using RNA expression analysis of rat liver and skeletal tissue (Rattus norvegicus, Berkenhout, 1769), we describe the expression profiles of 20 genes involved in mitochondrial maturation and ATP synthase biogenesis in detail between the 16th and 22nd day of gestation and the first 4 days of life. We observed that the most important expression shift occurred in the liver between the 20th and 22nd day of gestation, indicating that the fetus prepares for birth about two days before parturition. The detailed mechanism regulating the perinatal adaptation process is not yet known. Deeper insights in perinatal physiological development will help to assess mitochondrial dysfunction in the broader context of cell metabolism in preterm newborns or neonates with poor adaptation to extra-uterine life.
Keywords: protonové ATPasy; Pilot Projects; Muscle Development; novorozená zvířata; biogeneze organel; Female; vývoj svalů; Organelle Biogenesis; stanovení celkové genové exprese; ženské pohlaví; svaly; Animals, Newborn; těhotenství; potkani Wistar; játra; fyziologická adaptace; Animals; Adaptation, Physiological; Proton-Translocating ATPases; zvířata; pilotní projekty; Muscles; Rats, Wistar; Gene Expression Profiling; Pregnancy; Liver